Preparation method and application of double-layer garnet solid electrolyte
Through the preparation method of double-layer garnet solid electrolyte, the coating of molten metal lithium forms an ion-electron conductor layer, solving the problem of high interface impedance, improving the energy density and cycle stability of the lithium battery, and achieving better charging Discharge performance and lithium dendrites inhibitory effect.
Patent Information
- Application Number
- CN202210789310.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-06
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-07-06
AI Technical Summary
The interface impedance of the existing garnet-type solid electrolytes is too high, which limits the energy density and cycle stability of lithium-ion batteries. The production process is complex and the cost is high, making it difficult to achieve large-scale production.
Using the preparation method of double-layer garnet solid electrolyte, Li7-3xFexLa3Zr2O12 and Li7-yLa3Zr2-yTayO12 were prepared, and then pressed into sheets and calcined to form a double-layer solid electrolyte, and the surface of which was coated with molten metal lithium was formed. A layer of ion-electron conductor layer reduces interface impedance.
The impedance between the metal lithium negative electrode and the solid electrolyte is significantly reduced, the energy density and cycle stability of the lithium battery are improved, the utilization rate of lithium is increased, the generation of lithium dendrites is suppressed, and the charge and discharge performance is improved.
Smart Images

Figure CN115295869B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new materials and solid-state lithium batteries, and in particular to a preparation method of a double-layer garnet-type solid electrolyte and application thereof. Background Art
[0002] Traditional lithium-ion batteries are composed of graphite negative electrode materials, organic electrolytes, and LiCoOx positive electrode materials. The theoretical capacity of graphite negative electrode materials is only 372mAh g-1, and its initial lithium insertion potential is less than 0.1V, which is very close to the electrodeposition potential of metallic lithium. At high charge and discharge rates, lithium dendrites are easily precipitated on the surface of the graphite negative electrode and grow inside the electrolyte, penetrating the diaphragm to cause a short circuit in the battery, leading to safety accidents. In addition, organic electrolytes have the disadvantages of narrow electrochemical windows and difficulty in assembly, which limit the mass and volume energy density of lithium-ion batteries.
[0003] Using solid electrolytes to replace electrolytes is one of the effective measures to solve lithium dendrites, and it is expected to fundamentally solve the safety problem. Solid electrolytes should have high lithium ion conductivity, a wide chemical window, and good chemical stability to electrode materials. Among them, garnet-type solid electrolytes have the advantages of high conductivity (nearly 10-4S cm-1), stability to metallic lithium, and a wide electrochemical window (0-4V). It is one of the candidate electrolyte materials for the next generation of high-safety solid-state lithium batteries.
[0004] Excessive interfacial impedance is one of the main factors restricting the development of garnet-type solid electrolytes. Unlike electrolytes, the contact between solid electrolytes and solid electrodes is solid-solid contact, and the contact area is very limited, which severely limits the kinetic process at the electrode interface, resulting in excessive solid-solid interface impedance. A lot of research has been carried out on this, mainly reflected in: 1) Introducing an intermediate layer on the electrolyte surface, including metals such as Al (Science Advances, 2017, e1601659) and nitrides such as Li3N (Nano Letters, 2018, 18, 7414). This type of technology mainly deposits a thin layer on the electrolyte surface by different means. The thin layer can evenly coat the electrolyte and achieve good bonding with the electrolyte surface; at the same time, the lithium affinity of the thin layer is used to fully contact with metallic lithium, increase the effective contact area of the electrode electrolyte, and reduce the interfacial impedance. 2) Compounding inorganic solid electrolytes with organic solid electrolytes (Advanced Functional Materials, 2019, 29, 1805301). This type of method mainly uses the flexibility of the organic solid electrolyte itself to increase the solid-solid contact area. 3) Introducing graphite (Advanced materials, 2019, 31, e1807243), metal Zn (), etc. into the molten metal lithium negative electrode. This type of method mainly optimizes the surface energy of molten metal lithium and improves the wettability of the metal lithium negative electrode on the surface of the solid electrolyte, thereby increasing the solid-solid contact area and reducing the interface impedance. Although these methods can achieve certain effects, they have high requirements for production processes and equipment hardware, high production costs, limited improvement effects, and difficulty in large-scale production. New improvement strategies need to be further developed. For this reason, we propose a preparation method and application of a double-layer garnet solid electrolyte. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] In view of the deficiencies in the prior art, the present invention provides a preparation method of a double-layer garnet-type solid electrolyte and its application to solve the above-mentioned problems.
[0007] (II) Technical solution
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] A method for preparing a double-layer garnet-type solid electrolyte comprises the following steps:
[0010] Step 1: Prepare Li7-3xFexLa3Zr2O12 and Li7-yLa3Zr2-yTayO12;
[0011] Step 2: Press Li7-3xFexLa3Zr2O12 and Li7-yLa3Zr2-yTayO12 into sheets and calcine them to obtain a double-layer solid electrolyte.
[0012] Preferably, the preparation of Li7-3xFexLa3Zr2O12 in the first step is as follows: weigh Li, Fe, La, and Zr raw materials in a stoichiometric ratio, add a grinding aid and grind in a planetary ball mill to obtain a reddish-brown solution, place it in a drying oven at a temperature of 40 to 80°C and dry it into a brown powder, transfer the powder to a crucible, calcine it at a temperature of 600 to 1000°C, and crush it to obtain black-brown Li7-3xFexLa3Zr2O12.
[0013] Preferably, the preparation of Li7-yLa3Zr2-yTayO12 in the first step is as follows: weigh Li, La, Zr, and Ta raw materials in a stoichiometric ratio, add a grinding aid and grind in a planetary ball mill to obtain a white solution, place it in a drying oven at a temperature of 40 to 80°C and dry it into a white powder, transfer the powder to a crucible, calcine it at a temperature of 600 to 1000°C, and crush it to obtain light yellow Li7-yLa3Zr2-yTayO12.
[0014] Preferably, the preparation of the double-layer solid electrolyte in the second step is as follows: Li7-3xFexLa3Zr2O12 and Li7-yLa3Zr2-yTayO12 are pressed into sheets in a mass ratio of 1:0.1-1:1, and the obtained sheet-like solid electrolyte is calcined at a temperature of 1000-1300°C to obtain a double-layer solid electrolyte.
[0015] Preferably, the Li raw material is LiOH·H2O;
[0016] The Fe raw material is Fe2O3;
[0017] The raw material of La is La2O3;
[0018] The Zr raw material is ZrO2.
[0019] Preferably, the Li raw material is LiOH·H2O;
[0020] The raw material of La is La2O3;
[0021] The Zr raw material is ZrO2;
[0022] Ta raw material is Ta2O5.
[0023] Preferably, the composition of the double-layer solid electrolyte is Li7-3xFexLa3Zr2O12|Li7-yLa3Zr2-yTayO12, where 0.1≤x≤0.4, 0.2≤y≤0.6.
[0024] Preferably, x is 0.1≤x≤0.3, and y is 0.3≤y≤0.6.
[0025] Preferably, 0.3≤y≤0.5.
[0026] An application of a double-layer solid electrolyte comprises the following steps:
[0027] Step 1: polish the surface of a double-layer solid electrolyte with a diameter of 1 cm and a thickness of 2 mm with 2000-grit sandpaper, rinse with ethanol, and then dry;
[0028] Step 2: Heat 0.183 g of metallic lithium to 200° C. to obtain molten metallic lithium;
[0029] Step 3: Coat the molten metallic lithium on the surface of the double-layer solid electrolyte and obtain a lithium battery composite material after cooling.
[0030] (III) Beneficial effects
[0031] Compared with the prior art, the preparation method and application of the double-layer garnet solid electrolyte provided by the present invention have the following beneficial effects:
[0032] 1. The preparation method and application of the double-layer garnet solid electrolyte. Under the driving force of chemical reaction, metallic lithium can be more fully combined with the surface of the solid electrolyte, which is manifested in that the impedance of the metallic lithium negative electrode to the solid electrolyte is significantly reduced, thereby improving the energy density and cycle stability of the corresponding battery.
[0033] 2. The preparation method and application of the double-layer garnet-type solid electrolyte. The double-layer solid electrolyte material of the present invention forms an ion-electron conductor layer by bonding metallic lithium and a solid electrolyte, thereby reducing the specific surface area difference between the contact surface of the cathode material and the solid electrolyte, so that the double-layer solid electrolyte material of the present invention has smaller impedance and conductivity, and better charge and discharge performance.
[0034] 3. Preparation method and application of the double-layer garnet-type solid electrolyte. The present invention provides a double-layer solid electrolyte. The double-layer solid electrolyte of the present invention forms a coating by coating molten lithium metal on the surface of the solid electrolyte, thereby reducing the specific surface area difference between the contact surface of the negative electrode material and the solid electrolyte, so that the lithium metal negative electrode is better fitted on the surface of the solid electrolyte. The coating of the lithium metal and the solid electrolyte forms an ion-electron conductor layer that can conduct electrons and lithium ions, thereby increasing the utilization rate of lithium in the negative electrode, making the lithium ion flux and electric field at the interface uniformly distributed, and inhibiting the formation of lithium dendrites. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1The scanning electron microscope (SEM) images of the solid electrolytes of the embodiments of the present invention and the comparative examples;
[0036] Figure 2 It is a Mapping diagram of Embodiment 1 of the present invention;
[0037] Figure 3 The XRD diagrams of the solid electrolytes of the embodiments and comparative examples of the present invention are shown in FIG.
[0038] Figure 4 The SEM images of the interface between the solid electrolyte and lithium metal of the embodiment and the comparative example of the present invention are shown;
[0039] Figure 5 The AC impedance diagrams of the solid electrolytes of the embodiments of the present invention and the comparative examples;
[0040] Figure 6 It is a constant current cycle diagram of a symmetrical battery of an embodiment of the present invention and a comparative example;
[0041] Figure 7 This is a rate performance diagram of the all-solid-state battery of Example 1 of the present invention. DETAILED DESCRIPTION
[0042] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] Example
[0044] See also Figure 1-7 The method for preparing a double-layer garnet-type solid electrolyte provided by an embodiment of the present invention comprises the following steps:
[0045] (1)Li 7-3x FexLa3Zr 2O12 Preparation of (LFLZO): Li, Fe, La, and Zr raw materials in a stoichiometric ratio were weighed, and grinding aids were added to the mixture in a planetary ball mill to obtain a reddish-brown solution, which was then dried in a drying oven at temperature T1 to obtain brown powder. The powder was transferred to a crucible, calcined at temperature T2, and crushed to obtain black-brown Li 7-3x FexLa3Zr 2O12 .
[0046] (2) Preparation of Li7-yLa3Zr2-yTayO12 (LLZTO): Li, La, Zr and Ta raw materials in stoichiometric proportions were weighed, and grinding was performed in a planetary ball mill with the addition of a grinding aid to obtain a white solution, which was then dried in a drying oven at temperature T1 to obtain a white powder. The powder was transferred to a crucible, calcined at temperature T2, and crushed to obtain light yellow Li7-yLa3Zr2-yTayO12.
[0047] (3) Secondary sintering of solid electrolyte: The sintered Li7-3xFexLa3Zr2O12 and Li7-yLa3Zr2-yTayO12 are pressed into sheets according to a certain mass ratio of 1:0.1-1:1, and the obtained sheet-like solid electrolyte is calcined at T3 temperature to obtain a double-layer garnet-type solid electrolyte.
[0048] Among them, T1 is 40-80°C, T2 is 600-1000°C, and T3 is 1000-1300°C.
[0049] The Li raw material required for step (1) is LiOH·H2O, the Fe raw material is Fe2O3, the La raw material is La2O3, and the Zr raw material is ZrO2.
[0050] The Li raw material required for step (2) is LiOH·H2O, the La raw material is La2O3, the Zr raw material is ZrO2, and the Ta raw material is Ta2O5.
[0051] The composition of the double-layer solid electrolyte of the present invention is Li7-3xFexLa3Zr2O12|Li7-yLa3Zr2-yTayO12, wherein 0.1≤x≤0.4, 0.2≤y≤0.6.
[0052] x is preferably 0.1≤x≤0.3.
[0053] y is preferably 0.3≤y≤0.6, more preferably 0.3≤y≤0.5
[0054] Example 1
[0055] This embodiment provides an application of a double-layer garnet-type solid electrolyte prepared by the aforementioned method, which is applied to the preparation of a lithium battery composite material.
[0056] As a double-layer garnet-type solid electrolyte in an embodiment of the present invention, the double-layer solid electrolyte includes LFLZO and LLZTO, the Fe content in LFLZO is 0.1, the Ta content in LLZTO is 0.5, and the mass ratio of LFLZO to LLZTO is 0.5:1.
[0057] (1) A double-layer solid electrolyte with a diameter of 1 cm and a thickness of 2 mm was polished with 2000-mesh sandpaper, rinsed with ethanol, and dried;
[0058] (2) heating 0.183 g of metallic lithium to 200° C. to obtain metallic lithium in a molten state;
[0059] (3) coating the molten metal lithium obtained in step (2) on the surface of the double-layer solid electrolyte, and obtaining a lithium battery composite material after cooling.
[0060] Example 2
[0061] As an application of a double-layer garnet-type solid electrolyte (lithium battery composite material) provided in an embodiment of the present invention, this embodiment is substantially the same as Embodiment 1, except that the Fe content in LFLZO is 0.2.
[0062] Example 3
[0063] As an application of a double-layer garnet-type solid electrolyte (lithium battery composite material) provided in an embodiment of the present invention, this embodiment is substantially the same as Embodiment 1, except that the Fe content in LFLZO is 0.3.
[0064] Example 4
[0065] As an application of a double-layer garnet-type solid electrolyte (lithium battery composite material) provided in an embodiment of the present invention, this embodiment is substantially the same as Embodiment 1, except that the Fe content in LFLZO is 0.4.
[0066] Comparative Example 1
[0067] As a solid electrolyte of a comparative example of the present invention, the solid electrolyte is LFLZO, and the Fe content in LFLZO is 0.1.
[0068] The preparation method of the lithium battery composite material of this comparative example comprises the following steps:
[0069] (1) A LFLZO solid electrolyte with a diameter of 1 cm and a thickness of 2 mm was polished with 2000-mesh sandpaper, rinsed with ethanol, and dried;
[0070] (2) heating 0.183 g of metallic lithium to 200° C. to obtain molten metallic lithium;
[0071] (3) coating the molten metal lithium obtained in step (2) on the surface of the solid electrolyte, and obtaining a lithium battery composite material after cooling.
[0072] Comparative Example 2
[0073] As a solid electrolyte of a comparative example of the present invention, the solid electrolyte is LLZTO, and the Ta content in LLZTO is 0.5.
[0074] The preparation method of the lithium battery composite material of this comparative example comprises the following steps:
[0075] (1) The LLZTO solid electrolyte with a diameter of 1 cm and a thickness of 2 mm was polished with 2000-mesh sandpaper, rinsed with ethanol, and dried;
[0076] (2) heating 0.183 g of metallic lithium to 200° C. to obtain molten metallic lithium;
[0077] (3) coating the molten metal lithium obtained in step (2) on the surface of the solid electrolyte, and obtaining a lithium battery composite material after cooling.
[0078] Test Case
[0079] (1) Material characterization:
[0080] The double-layer solid electrolytes prepared in Examples 1 to 4 and Comparative Example 2 were characterized by scanning electron microscopy (SEM). Figure 1 As shown in the figure, the grain size increases with the increase of Fe content. Finally, when the Fe content is 0.4, obvious voids appear at the grain boundaries. A mapping test was performed on Example 1. Figure 2 As shown in FIG. 1 , it is found that Fe is mainly distributed on both sides, Ta is mainly distributed in the middle, and La is evenly distributed. XRD characterization is performed on Examples 1 to 4 and Comparative Example 2. Figure 3 As shown, Examples 1 to 4 and Comparative Example 2 all synthesized garnet-type solid electrolytes with a cubic phase structure of space group Ia-3d. SEM characterization was performed on the interface between the solid electrolytes prepared in Example 1 and Comparative Example 2 and lithium metal. The results are as follows Figure 4 As shown, the interface between the solid electrolyte and the metallic lithium in Example 1 is tightly fitted without voids, while a larger void exists at the interface between the solid electrolyte and the metallic lithium in Comparative Example 2, which proves that the modification method in Example 1 can improve the contact between the solid electrolyte and the lithium metal.
[0081] (2) Performance test:
[0082] The AC impedance test of the symmetrical battery was carried out on Comparative Example 2 and Examples 1 to 3. The results are as follows: Figure 5 As shown, Figure 5 (a) is the AC impedance diagram of the solid electrolyte of Comparative Example 2, Figure 5 (b) is the AC impedance diagram of the solid electrolyte of Example 1, Figure 5 (c) is the AC impedance diagram of the solid electrolyte of Example 2, Figure 5(d) is the AC impedance diagram of the solid electrolyte of Example 2. The interface ion transfer impedance of Comparative Example 2 is 2350Ω·cm-2, the interface ion transfer impedance of Example 1 is 365.2Ω·cm-2, the interface ion transfer impedance of Example 2 is 509.0Ω·cm-2, and the interface ion transfer impedance of Example 3 is 682.3Ω·cm-2. This shows that the double-layer solid electrolyte prepared by doping Fe in LLZO can reduce the interface ion transfer impedance between the solid electrolyte and the lithium metal negative electrode. Moreover, by comparing Examples 1 to 3, it is found that the AC impedance of Example 1 is relatively lower, indicating that Example 1 is the best ratio.
[0083] The solid electrolytes in Comparative Example 2 and Examples 1 to 4 were assembled into symmetrical batteries and subjected to constant current charge and discharge tests. The results are as follows: Figure 6 As shown, Figure 6 (a) is a constant current cycle diagram of the symmetrical battery of Comparative Example 2, Figure 6 (b) is a constant current cycle diagram of the symmetrical battery of Example 1, Figure 6 (c) is a constant current cycle diagram of the symmetrical battery of Example 2, Figure 6 (d) is a constant current cycle diagram of the symmetrical battery of Example 3, Figure 6 (e) is a constant current cycle diagram of the symmetrical battery of Example 4. Figure 6 It can be seen that at a current density of 0.1mA·cm-2, the symmetrical battery of Comparative Example 2 will short-circuit, indicating that the solid electrolyte prepared in Comparative Example 2 cannot inhibit the formation of lithium dendrites. The voltage of the symmetrical battery in Example 1 exceeded 0.1V in the first few cycles, and the voltage was stabilized at 0.009V in the subsequent 400h. In Example 2, the voltage of the symmetrical battery decreased from 0.15V to 0.013V in the first 80h, accompanied by internal micro-short-circuit noise, and the voltage was stabilized at 0.013V in the subsequent 300h. In Examples 3 to 4, the voltage of the symmetrical battery decreased from 0.5V to 0.05V and 0.15V in the first 80h, accompanied by severe internal micro-short-circuit noise. It shows that at this time, the lithium dendrites have pierced the LFLZO layer, but not the LLZTO layer. After comparison, it was found that the solid electrolyte of Example 1 has the best effect in inhibiting lithium dendrites.
[0084] The solid electrolyte in Example 1 was assembled into a solid-state battery, and the rate performance was tested. The results are as follows: Figure 7As shown. The discharge specific capacity of the solid-state battery at the charge and discharge current density of 0.1C, 0.25C, 0.5C, 0.75C and 1C are 154mAh·g-1, 142mAh·g-1, 125mAh·g-1, 111mAh·g-1 and 92mAh·g-1 respectively. Taking the 0.1C discharge specific capacity as the standard value, only about 60% of the electricity can be discharged at the maximum rate. When the charge and discharge current density is restored to 0.1C, the discharge specific capacity can be restored to 153mAh·g-1, which is equivalent to the initial discharge specific capacity, proving that the solid-state battery prepared by the material of the present invention has good cycle rate performance, confirming that lithium dendrites on the lithium metal|garnet electrolyte have been successfully suppressed.
[0085] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a double-layer garnet-type solid electrolyte, characterized in that: The following steps are involved: first step: Prepare Li 7-3x FexLa3Zr2O 12 and Li7-yLa3Zr2-yTayO 12 Two materials; Step 2: Li 7-3x FexLa3Zr2O 12 and Li7-yLa3Zr2-yTayO 12 The two materials are pressed into sheets and calcined to obtain a double-layer garnet-type solid electrolyte; x is 0.1≤x≤0.3, and y is 0.3≤y≤0.
6.
2. The method for preparing a double-layer garnet-type solid electrolyte according to claim 1, characterized in that: In the first step, Li 7-3x FexLa3Zr2O 12 The preparation steps are as follows: weigh the raw materials of Li, Fe, La, and Zr in a stoichiometric ratio, add a grinding aid and grind in a planetary ball mill to obtain a reddish-brown solution, place the solution in a drying oven at a temperature of 40 to 80°C and dry it into brown powder, transfer the powder into a crucible, calcine it at a temperature of 600 to 1000°C, and crush it to obtain a black-brown Li 7- 3x FexLa3Zr2O 12 .
3. The method for preparing a double-layer garnet-type solid electrolyte according to claim 2, characterized in that: The Li raw material is LiOH·H2O; the Fe raw material is Fe2O3; the La raw material is La2O3; and the Zr raw material is ZrO2.
4. The method for preparing a double-layer garnet-type solid electrolyte according to claim 1, characterized in that: Step 1 7-3x FexLa3Zr2O 12 The preparation steps are as follows: weigh Li, La, Zr, and Ta raw materials in a stoichiometric ratio, add a grinding aid, grind in a planetary ball mill to obtain a white solution, place the solution in a drying oven at a temperature of 40 to 80°C and dry it into a white powder, transfer the powder to a crucible, calcine at a temperature of 600 to 1000°C, and crush it to obtain a light yellow Li7-yLa3Zr2-yTayO 12 .
5. The method for preparing a double-layer garnet-type solid electrolyte according to claim 4, characterized in that: The Li raw material is LiOH·H2O; the La raw material is La2O3; the Zr raw material is ZrO2; and the Ta raw material is Ta2O5.
6. The method for preparing a double-layer garnet-type solid electrolyte according to claim 1, characterized in that: The preparation steps of the double-layer solid electrolyte in the second step are as follows: Li 7-3x FexLa3Zr2O 12 With Li7-yLa3Zr2-yTayO 12 The two materials are pressed into sheets in a mass ratio of 1:(0.1-1), and the obtained sheet-like solid electrolyte is calcined at a temperature of 1000-1300° C. to obtain a double-layer solid electrolyte.
7. The method for preparing a double-layer garnet-type solid electrolyte according to claim 1, characterized in that: The y is 0.3≤y≤0.
5.
8. Application of the method for preparing a double-layer garnet-type solid electrolyte according to claim 1, characterized in that: The following steps are involved: Step 1: polish the surface of a double-layer garnet-type solid electrolyte with a diameter of 1 cm and a thickness of 2 mm with 2000-grit sandpaper, rinse with ethanol, and then dry; Step 2: Heat 0.183 g of metallic lithium to 200° C. to obtain molten metallic lithium; Step 3: Coat the molten metallic lithium on the surface of the double-layer solid electrolyte and obtain a lithium battery composite material after cooling.
